PENERAPAN TEKNOLOGI MESIN PEMOTONG SINGKONG UNTUK MENINGKATKAN PRODUKTIVITAS UMKM DI DUSUN MIRI, POLOKARTO, SUKOHARJO - Guritno, Muhammad Wahyu Suryo; Muhajir, Muhammad; Saputra, Nurirwan (Universitas PGRI Yogyakarta, 2024)
This research aims to design and develop an efficient and effective cassava-cutting machine for use by MSME players in Miri, Bulu, Polokarto, Sukoharjo Regency. Cassava is one of the important natural resources in the region, and cutting cassava manually often takes significant time and effort. The research method used is a field survey to identify the needs and problems faced by MSMEs in Miri sub-village. The results of this survey became the basis for designing a cassava-cutting machine that suits local conditions. This machine is designed by considering aspects of ergonomics, efficiency, and user safety. The results showed that the designed cassava cutting machine can cut cassava quickly and accurately, reducing the time and effort required in the cutting process. In addition, this cassava-cutting machine has the potential to increase the productivity of MSMEs. With the use of this machine, it is expected to reduce heavy manual labor and allow MSME players to focus on other more value-added activities. This research is a positive contribution to supporting the development of MSMEs in Miri sub-village and can be a model for the development of similar machines in other areas. This cassava-cutting machine is expected to provide significant benefits for MSME actors. Keyword: Cassava, Cutting Machine, MSMEs